2021
DOI: 10.3390/metabo11070412
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Analysis to Assess Oxidative Stress in Acute Coronary Syndrome and Acute Stroke Patients

Abstract: Alterations in lipid metabolism mediated by oxidative stress play a key role in the process of atherosclerosis and superimposed thrombosis; these can lead to acute coronary syndrome (ACS) and acute ischemic stroke (AIS). Multiple studies have shown that the formation of atheromatous lesions is initiated by oxidation of low-density lipoproteins incorporated into the intima of the vessel wall. Here, we studied lipids in plasma samples from three cohorts: 61 patients with ACS (group A), 49 patients with AIS (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…In our previous study [4], multiple significant changes in lipid patterns were observed five days after ACS. With regards to limited data in the literature, we were interested in long-term trends in respective patients' plasma lipidome.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous study [4], multiple significant changes in lipid patterns were observed five days after ACS. With regards to limited data in the literature, we were interested in long-term trends in respective patients' plasma lipidome.…”
Section: Discussionmentioning
confidence: 80%
“…Blood samples were collected from 17 patients 3-6 days after ACS (group B) and from the same patients three years after (group AC) who were diagnosed at the Central Military Hospital, University Military Hospital in Prague, Czech Republic (Table 2). These samples represent subgroups of 61 plasma samples that were analyzed from patients undergoing percutaneous coronary intervention (PCI) due to ACS described in our previous work [4]. Blood samples were collected via venipuncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OFRs lead to the formation of lipid peroxides which alter cell membranes by increasing incorporation of cholesterol and oxidized free fatty acids (FFAs) and low-density lipoproteins [ 78 ]. As for atherogenesis [ 90 ], chronic oxidative stress in the placenta leads to impaired circulation and diffuse maternal endothelial cell dysfunction. Abnormal endothelial function exemplified by increased circulating levels of fibronectin and von Willebrand factor, markers of endothelial cell injury, is found in women with PE.…”
Section: Consequences For the Pregnant Womanmentioning
confidence: 99%
“…Oxylipins influence numerous physiological and pathological processes [ 20 , 21 , 22 ]. Furthermore, the function of oxylipins in acute coronary syndrome (ACS) or other cardiovascular disorders has been reported [ 23 , 24 , 25 , 26 ]. Here, we demonstrated altered oxylipins in individuals with AD and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%